A Simple Lyapunov Function Based Control Strategy for Coordinated Transient Stability Enhancement of Power Systems - Muluh, Fombu Andrew; Sanjong Dagang, Clotaire Thierry; Jean Pierre, Pesdjock Mathieu; Lionel Leroy, Sonfack; Godpromesse, Kenne (IAES Indonesian Section, 2024)
Transient stability is still a serious impediment in power system operation due to their highly nonlinear nature. Over the last decades, a vast number of diverse nonlinear control algorithms for sub-controllers located at the generator subsystem and transmission lines have been developed to boost power system stability. However, for an effective and feasible operation of these power systems, coordination of these sub-controllers is very essential. In this paper, a simple direct Lyapunov based approach for coordinated control is proposed for global enhancement of power system stability. The proposed control scheme is achieved through the coordination of Lyapunov based decentralized steam valve, excitation and SSSC adaptive controllers. To test the efficacy of the proposed scheme, several comparisons in multi-machine fault scenarios with other design coordinated approaches are presented. Numerical simulations demonstrate the swiftness and efficacy of the proposed control scheme in boosting global stability.